Preparation of biological sustained-release nanocapsules and explore on algae-killing properties - Jinyun Li; Ming Guo; Yiping Wang; Bihuan Ye; Youwu Chen; Xuejuan Yang (Journal of Advanced Research, 2021)
Introduction: Green algae seriously affect the quality and yield of Torreya grandis, it is important to explore new, environmentally friendly ways to control it. Objectives: The present study aimed at preparing sustained-release algae-killing nanocapsules without pollution to the environment. Methods: In this work, sodium carboxymethylcellulose (CMC), sodium alginate (SA), and chitosan (CTS) were used as raw materials in acylation reaction with the photosensitive catalytic material iron octaaminophthalocyanine (T) to generate the photoactive bio-based materials T-CMC, T-SA, and T-CMCS. Cinnamaldehyde and 2-aminobenzimidazole were combined using chemical grafting to produce a new algicide, and then formed nanocapsules by phase separation. The molecular structure of products was characterized by UV–Vis, FTIR, and NMR (1H NMR, 13C NMR). The particle size of the nanocapsules was determined by Zeta particle size analysis and TEM; DSC was used to investigate the thermal stability; The encapsulation efficiency and sustained-release performance were determined by HPLC. Then the phytotoxic of the new algicide was measured. Results: The bio-based nanocapsules was successfully synthesized, which had a particle size of 10–30 nm and was stable at 40 °C. The encapsulation efficiency of the nanocapsules was 48.77%, the cumulative release rate was 83%, and the new algicide killed the green algae in a dose-dependent way. Conclusions: The bio-based nano capsule is a new and valuable Sustained-release capsule, which is the method of green algae.